Developing a Strategic Model of Internal Crisis Communication: Empirical Evidence from Nigeria. Issue 3 (27th May 2019) - Adamu, Adamu Abbas; Mohamad, Bahtiar
ABSTRACT: The internal aspects of crisis communication have been identified as a growing area of research in crisis management; however, there remains a paucity of empirical studies dedicated to this dimension of crisis communication. The objective of this study is to examine the influence of social media usage, leadership, crisis responsibility, and error management culture on internal crisis communication. In addition, this study investigates how internal crisis communication impacts affective organizational commitment and perceived organizational support. A survey was conducted of 325 employees of an electricity distribution company. Findings indicate that leadership and error management culture are significantly related to internal crisis communication. In contrast, social media usage and crisis responsibility do not have a significant effect on internal crisis communication. However, internal crisis communication is positively related to affective organizational commitment and perceived organizational support. The results of this study suggest that crisis managers should emphasize the need for organizational leaders to include employees as primary stakeholders in crisis management. Finally, this study demonstrates the need for researchers to further investigate different social media tools to assess their impact on internal crisis communication.